Scanning electron microscopy comparison of the resin–dentin interface using different specimen preparation methods - Augusto, Marina G. [UNESP]; Dantas, Debora C. B. [UNESP]; de Andrade, Guilherme S. [UNESP]; Matuda, Amanda G. N. [UNESP]; Lopes, Stephanie R. [UNESP]; Barcellos, Daphne C. [UNESP]; Pucci, Cesar R. [UNESP] (Wiley, 2020)
Microscopy has been widely used to complement the data of studies related to dentin bonding; however, different specimen preparation methods may influence the analysis. Aiming to contribute to the reported scenario, this study evaluated the effect of two specimen-sectioning methods (cleavage and diamond disk cut) on the quality of the scanning electron microscopy (SEM) images. Four crowns of human molars were selected and had an area of approximately 6 mm2 of dentin exposed. They were then divided into two groups according to the universal adhesive application: total and self-etching modes. Then, composite blocks were built up and the specimens were stored in deionized water to allow the postcuring. The specimens were further divided according to the sectioning method: cleavage or diamond disk cut. Four specimens were obtained from each tooth. They were desiccated, placed on aluminum stubs, sputter-coated with gold, and observed in a scanning electron microscope, with ×2000 of magnification. The quality of the SEM images were evaluated by two calibrated examiners and classified into four scores (1–4). Mann–Whitney test (p <.05) showed that the diamond disk provided significantly higher scores than cleavage, whereas no significant difference was observed when comparing the total-etching and self-etching modes of application. The diamond disk cut method is preferable to the cleavage method to ensure the quality of the SEM analysis in studies involving the resin–dentin interface.
Keywords: adhesive system; bonding; dentin; scanning electron microscopy